Service Quality of Teaching Vocational Education and Training (TVET) and Student’s Satisfaction in Nigeria - Wasiu Abiodun Makinde; Tolulope Oluwatosin Bamiro (Journal of Pedagogy and Education Science, 2023)
Technical, Vocational, Education and Training (TVET) has been identified as an effective strategy for improving socio-economic development of both developing and developed nations. This study aims at assessing the student’s experience of service quality of TVET in the Federal Polytechnic Ilaro, Nigeria. The study reviewed concept of service quality and TVET, reviewed of previous findings from related studies and adopted SERVQUAL model as framework for the study. The population of the study comprised of about 10,250 student during 2021/2022 academic session. Data collected were analysed through descriptive and inferential statistics. The study discovered that physical facilities, comfortable classroom, adequate academic resources and appearance of physical facilities are highly ranked tangibility. Lecturer’s good knowledge, lecturer’s politeness and security measures are highly ranked in assurance and support staff fairness, lecturers sincere interest on student and lecturer’s teaching capability are highly ranked reliability. Also, lecturer’s adequate capacity, treatment of complaints by student and support staff availability are highly ranked responsiveness and, polytechnic fair treatment, support staff attention to students and lecturer’s support to individual students are highly ranked empathy. Therefore, the study concluded that students are experiencing service quality of TVET.